Mutational Analysis of Bacillus subtilis Glutamine Phosphoribosylpyrophosphate Amidotransferase Propeptide Processing - Li, Songtao (American Society for Microbiology, 1999)
Glutamine phosphoribosylpyrophosphate amidotransferase from Bacillus subtilis is a member of an N-terminal nucleophile hydrolase enzyme superfamily, several of which undergo autocatalytic propeptide processing to generate the mature active enzyme. A series of mutations was analyzed to determine whether amino acid residues required for catalysis are also used for propeptide processing. Propeptide cleavage was strongly inhibited by replacement of the cysteine nucleophile and two residues of an oxyanion hole that are required for glutaminase function. However, significant propeptide processing was retained in a deletion mutant with multiple defects in catalysis that was devoid of enzyme activity. Intermolecular processing of noncleaved mutant enzyme subunits by active wild-type enzyme subunits was not detected in hetero-oligomers obtained from a coexpression experiment. While direct in vitro evidence for autocatalytic propeptide cleavage was not obtained, the results indicate that some but not all of the amino acid residues that have a role in catalysis are also needed for propeptide processing.